Time to return to full training and recurrence of rectus femoris injuries in elite track and field athletes 2010–2019; a 9‐year study using the British Athletics Muscle Injury Classification. (31st March 2022) - McAleer, Stephen; Macdonald, Ben; Lee, Justin; Zhu, Wilbur; Giakoumis, Michael; Maric, Tanya; Kelly, Shane; Brown, James; Pollock, Noel
Abstract: Rectus femoris (RF) injuries are common in sports requiring maximal acceleration and sprinting. The British Athletics Muscle Injury Classification (BAMIC) describes acute muscle injury based on the anatomical site of injury and has been associated with return to play in hamstring and calf muscle injury. The aim of this study was to describe and compare the time to return to full training (TRFT) and injury recurrence for BAMIC‐classified RF injuries sustained by elite track and field (T&F) athletes over a 9‐year period. All rectus femoris injuries sustained by elite T&F athletes on the British Athletics World Class Program between September 2010 and September 2019 that were investigated with an MRI within 7 days of acute onset anterior thigh pain were included. Injuries were graded from the MRI by a specialist musculoskeletal radiologist using the BAMIC, and TRFT and injury recurrence were determined by evaluation of the Electronic Medical Record. Athlete demographics and World Athletics event discipline were recorded. Specific injury details including mechanism, location of injury, and whether surgical or rehabilitation management was undertaken were recorded. There were 38 RF injuries in 27 athletes (24.7 ± 2.3 years; 10 male, 17 female). Average TRFT for rehabilitation managed cases was 20.4 ± 14.8 days. Grade 1 injuries had significantly shorter TRFT compared with grades 2 ( p  = 0.04) and 3 ( p  = 0.01). Intratendinous (c) and surgically managed RF injuries each had significantly longer TRFT compared with other injury classes ( p  < 0.001). Myofascial (a) injuries had reduced repeat injury rates compared with b or c classes ( p  = 0.048). Grade 3 injuries had an increased repeat injury rate compared with other grades ( p  = 0.02). There were 4 complete (4c) proximal free tendon injuries sustained during sprinting and all in female athletes. The average TRFT for RF injuries in elite T&F is similar to that previously identified in elite football and Australian Rules. Similar to previous research in hamstring and calf injury, RF injuries extending into the tendon (BAMIC class c) had delayed TRFT which may reflect the longer duration required for tendon healing and adaptation. Grade 3 injuries had in increased repeat injury rate compared with grades 1 and 2. The BAMIC diagnostic framework may provide useful information for clinicians managing rectus femoris injuries in T&F.